Interim analyses from a randomised controlled trial to improve visual processing speed in older adults: the Iowa Healthy and Active Minds Study. Issue 2 (21st November 2011) - Wolinsky, Fredric D; Vander Weg, Mark W; Howren, M Bryant; Jones, Michael P; Martin, Rene; Luger, Tana M; Duff, Kevin; Dotson, Megan M
Abstract : Objectives: The Iowa Healthy and Active Minds Study is a four-arm randomised controlled trial of a visual processing speed training programme ( Road Tour ). This article presents the preplanned interim results immediately after training (6–8 weeks post-randomisation) for the primary outcome. Design: Within two age strata (50–64 vs ≥65), 681 men and women attending general internal and family medicine clinics were randomised to four training groups: (1) supervised, on-site standard (10 h) dose of Road Tour training; (2) supervised, on-site standard dose of Road Tour training with 4 h of subsequent booster training scheduled to occur at 11 months post-randomisation (ie, no booster training had occurred at the time of this interim analysis); (3) supervised, on-site standard dose of attention control (crossword puzzles) training and (4) self-administered, at-home standard dose of Road Tour training. The primary outcome was the Useful Field of View (UFOV) test. Three intent-to-treat interim analyses were conducted, including (1) multiple linear regression models of composite UFOV scores using Blom rank transformations, (2) general linear mixed effects models and (3) multiple logistic regression models among the 620 participants (91%) with complete data. Results: In the linear regression analyses of both age strata, random assignment to any Road Tour training group versus the attention control group was significant (p<0.001), with an effect size of −0.558 (adjusted for the Blom rank transformed UFOV score at randomisation). Similar results were obtained for each Road Tour group and within each age stratum and from the general linear and logistic regression models. Conclusions: Assignment to a standard dose of Road Tour training yielded medium-sized post-training improvements in visual processing speed. Road Tour was equally effective whether administered under laboratory supervision or self-administered in the patient's home and for participants in both age strata (50–64 vs ≥65). Clinical trial registration number: NCT01165463.